Dual functions of mammalian olfactory sensory neurons as odor detectors and mechanical sensors - Grosmaitre, Xavier (2007)
Most sensory systems are primarily specialized to detect one sensory modality. Here we report that olfactory sensory neurons (OSNs) in the mammalian nose can detect two distinct modalities transmitted by chemical and mechanical stimuli. As revealed by patch-clamp recordings, many OSNs respond not only to odorants, but also to mechanical stimuli delivered by pressure ejections of odor-free Ringer solution. The mechanical responses correlate directly with the pressure intensity and show several properties similar to those induced by odorants, including onset latency, reversal potential and adaptation to repeated stimulation. Blocking adenylyl cyclase or knocking out the cyclic nucleotide–gated channel CNGA2 eliminates the odorant and the mechanical responses, suggesting that both are mediated by a shared cAMP cascade. We further show that this mechanosensitivity enhances the firing frequency of individual neurons when they are weakly stimulated by odorants and most likely drives the rhythmic activity (theta oscillation) in the olfactory bulb to synchronize with respiration.